Acute toxicity study and wound healing potential of Gynura procumbens leaf xtract in rats - Zahra, Abdulqadir Amin; Kadir, Farkaad Abdul; Mahmood, A.A.; Al Hadi, A.A.; Suzy, S.M.; Sabri, S.Z.; Latif, I.I.; Ketuly, Kamal Aziz (Academic Journals, 2011)
This study was conducted to evaluate the effects of topical application of ethanol extract of Gynura procumbens leaf extract on the rate of wound healing closure and histology of wound area. An area of uniform wound 2.00 cm in diameter using circular stamp was excised from the nape of the dorsal neck of all rats with the aid of round seal. The animal groups were topically treated with 0.2 ml of each vehicle (gum acacia),Intrasite gel,100 and 200 mg/ml of ethanol extract,respectively.Macroscopically,wound dressed with G. procumbens leaf extract and Intrasite gel significantly healed earlier than those treated with vehicle. On day 14 post-surgery, 6 animals from each group were sacrificed and histological analysis of wounds area showed that wounds dressed with leaf extract showed comparatively less scar width at wound closure and granulation tissue contained less inflammatory cells and more collagen with angiogenesis compared to wounds dressed with vehicle. Furthermore, acute toxicity study has indicated no mortality with 5 g/kg dose of G. procumbens leaf extract in Sprague Dawley and did not produce any major clinical signs of toxicity. In conclusion, wounds dressed with leaf extract significantly enhanced and accelerated the rate of wound healing enclosure in rats. © 2011 Academic Journals.